2020
DOI: 10.1007/s42977-020-00015-7
|View full text |Cite
|
Sign up to set email alerts
|

Biologia Futura: landscape perspectives on farmland biodiversity conservation

Abstract: European nature conservation has a strong focus on farmland harbouring threatened species that mainly co-occur with traditional agriculture shaped way before the green revolution. Increased land-use intensity in agriculture has caused an alarming decline in farmland biodiversity during the last century. How can a landscape perspective contribute to fostering our understanding on causes and consequences of farmland biodiversity decline and improving the effectiveness of conservation measures? To answer these qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…The high cover of autonomous specialists on kurgans suggests that these habitats can act as terrestrial habitat islands as previous studies found autonomous reproduction was characteristic to islands (Grossenbacher et al, 2017;Ottaviani et al, 2020). The high proportion of autonomous species on oceanic islands was first proposed by Baker (known as Baker's law;Baker, 1955), who argued that on islands species with uniparental reproduction have a considerable colonization advantage. As colonization is often achieved by only a few individuals, finding mates can be challenging in the early phase of establishment due to the small population size.…”
Section: Plant Traits Of Specialist Species Across the Habitat Typesmentioning
confidence: 87%
See 1 more Smart Citation
“…The high cover of autonomous specialists on kurgans suggests that these habitats can act as terrestrial habitat islands as previous studies found autonomous reproduction was characteristic to islands (Grossenbacher et al, 2017;Ottaviani et al, 2020). The high proportion of autonomous species on oceanic islands was first proposed by Baker (known as Baker's law;Baker, 1955), who argued that on islands species with uniparental reproduction have a considerable colonization advantage. As colonization is often achieved by only a few individuals, finding mates can be challenging in the early phase of establishment due to the small population size.…”
Section: Plant Traits Of Specialist Species Across the Habitat Typesmentioning
confidence: 87%
“…Land use intensification leading to the loss and fragmentation of natural habitats is considered one of the major threats to biodiversity on local, regional and global scales. In intensively used landscapes, the remnants of formerly widespread natural habitats could persist within the few protected areas, and in small fragments surrounded by intensive croplands, forest plantations or urban areas (Auffret et al, 2015;Batáry et al, 2020;Deák et al, 2020a). This phenomenon is especially valid for dry grasslands often harboring extremely high herbaceous plant diversity and a high number of endemic species (Dengler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2020; Batáry et al . 2020), but that also key plant species with specific traits (e.g. high nutritional value; Filipiak 2019; Lawson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach would require less compensation subsidies for farmers compared to non-productive measures such as flowering fields. Hence, conservation and management of pollinators and pollination services in arable land dominated landscapes should not be aimed at maximising the amount of flowering fields or strips, but should also foster organic farming including flower-rich winter cereals (Batáry et al 2020).…”
Section: Discussionmentioning
confidence: 99%